2021
DOI: 10.1038/s41598-021-93364-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of the black tiger shrimp (Penaeus monodon) reveals insights into immune development in their early life stages

Abstract: With the rapid growth in the global demand, the shrimp industry needs integrated approaches for sustainable production. A high-quality shrimp larva is one of the crucial key requirements to maximize shrimp production. Survival and growth rates during larval development are often criteria to evaluate larval quality, however many aspects of gene regulation during shrimp larval development have not yet been identified. To further our understanding of biological processes in their early life, transcriptomic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 94 publications
1
11
0
1
Order By: Relevance
“…MjSerp1 has been shown to play a direct effector role in the bacterial clearance of M. japonicus (Zhao et al, 2014). The immune-related pathways are ECM-receptor interactions, endocytosis, NF-kappa B signaling pathway, Toll and Imd signaling pathways and phagosome, which were consistently seen in both Zoea larvae and adults, implying that innate immunity against bacterial invasion may exist in zoea larvae, which is consistent with the findings of (Angthong et al, 2021).…”
Section: A B Figuresupporting
confidence: 82%
See 3 more Smart Citations
“…MjSerp1 has been shown to play a direct effector role in the bacterial clearance of M. japonicus (Zhao et al, 2014). The immune-related pathways are ECM-receptor interactions, endocytosis, NF-kappa B signaling pathway, Toll and Imd signaling pathways and phagosome, which were consistently seen in both Zoea larvae and adults, implying that innate immunity against bacterial invasion may exist in zoea larvae, which is consistent with the findings of (Angthong et al, 2021).…”
Section: A B Figuresupporting
confidence: 82%
“…During the period of Zoea larvae, the larvae rely on external food sources and are more sensitive to external environmental impacts, particularly infections by pathogenic Vibrio, which hinder larval growth. It has been reported that transcriptomic sequencing analysis has been performed throughout the early developmental stages of shrimp with the aim of comparatively analyzing the physiological changes during shrimp metamorphosis (Wei et al, 2014;Angthong et al, 2021). At present, majority of the research have focused on the adult stage, with few studies investigating the anti-vibrio immunity in the early stages of shrimp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics of the experimental shrimp, including species, life stage, genetic and geographical source, stress, and preexisting pathogen infections can influence the dynamics of disease expression. 45,47,58,59 Detailed reporting of such metadata in published PCEs will also enable progressive knowledge development for largerscale comparative meta-analyses, such as for understanding speciesand population-level responses to pathogen challenges.…”
Section: Host: the Shrimpmentioning
confidence: 99%